Neuronal MD2 induces long-term mental impairments in septic mice by facilitating necroptosis and apoptosis - Fan, Zhongmin; Ma, Hongwei; Li, Yi; Wu, You; Wang, Jiajia; Xiong, Lize; Fang, Zongping; Zhang, Xijing (Frontiers in Pharmacology, 2022)
Sepsis-associated encephalopathy (SAE) is a complication of sepsis with high morbidity rates. Long-lasting mental health issues in patients with SAE result in a substantial decrease in quality of life. However, its underlying mechanism is unclear, and effective treatments are not available. In the current study, we explored the role of apoptosis and necroptosis related to mental dysfunction in sepsis. In a mouse model of sepsis constructed by cecal ligation and puncture (CLP), altered behavior was detected by the open field, elevated-plus maze and forced swimming tests on the fourteenth day. Moreover, apoptosis- and necroptosis-associated proteins and morphological changes were examined in the hippocampus of septic mice. Long-lasting depression-like behaviors were detected in the CLP mice, as well as significant increases in neuronal apoptosis and necroptosis. Importantly, we found that apoptosis and necroptosis were related according to Ramsay’s rule in the brains of the septic mice. Inhibiting myeloid differentiation factor 2 (MD2), the crosstalk mediator of apoptosis and necroptosis, in neurons effectively reduced neuronal loss and alleviated depression-like behaviors in the septic mice. These results suggest that neuronal death in the hippocampus contributes to the mental impairments in SAE and that inhibiting neuronal MD2 is a new strategy for treating mental health issues in sepsis by inhibiting necroptosis and apoptosis.